ChemInform Abstract: Nanometric Solid Solutions of the Fluorite and Perovskite Type Crystal Structures: Synthesis and Properties. Issue 28 (21st June 2013) - Boskovic, Snezana; Zec, Slavica; Matovic, Branko; Dohcevic‐Mitrovic, Zorana; Popovic, Zoran; Zinkenvich, Matvei; Aldinger, Fritz; Krstic, Vladimir
Abstract Review: 12 refs.